Design of Islamic Religious Education (PAI) Curriculum Development at the Al-Ihsan Private Islamic High School (MAS) in Riau - Andre Wahyudi (Konsultan Jurnal Ilmiah Indonesia, 2025)
A curriculum is a collection of plans and arrangements related to objectives, teaching materials, and methods used as guidelines for implementing learning activities to achieve educational goals. This paper aims to describe how the design and development of the Islamic Religious Education curriculum at the Al-Ihsan Private Islamic Senior High School in Riau is relevant to the needs of students in a modern and multicultural era. The development of this Islamic Religious Education curriculum is expected to shape students who are pious, caring, and leaders, not merely possessing broad Islamic knowledge. This study used a descriptive qualitative approach, with data collection techniques through field observations and interviews with the Deputy Head of Curriculum and Islamic Religious Education teachers. The results indicate that designing a relevant Islamic Religious Education curriculum must consider objectives, teaching materials, learning methods, and learning evaluation.